Temporal and structural characteristics of different attack techniques in volleyball - Jaitner, T.; Brach, C. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
A process oriented approach was chosen to identify attack techniques in Volleyball. Male subjects were filmed with two high speed video cameras while they performed three attack techniques. Subject's movement was described by the time courses of angles and angular velocities of the main joints and analyzed by a procedure including distance measures and cluster analysis. Cluster analysis classified movement patterns of spikes, and top spin shots, by individual while patterns of lobs were mainly grouped by technique criteria. Except for the quick attacker, lobs are identified if only variables are considered that describes the movement of the arm during take off. From a practical view, the results suggest that a defender should focus on the arm of the attacker during take off to recognize the attackers intention early.